Study on Curing Mechanism of Magnesium Phosphate Cement to Contaminated Soil - Yuanyuan Li; Shibo Jia; Jiang Liu (Chemical Engineering Transactions, 2018)
Heavy metal pollution poses a threat to environment and human health in modern times. In order to avoid it, the curing mechanism of magnesium phosphate cement to contaminated soil under acid rain is studied in this paper. The macro-micro test, leaching test and other tests are adopted to observe the changes of the test project from the micro-angle. With the continuous progress of hydration reaction of magnesium phosphate cement, the ability of acid and corrosion resistance of contaminated soil is greatly improved. Using magnesium phosphate cement can effectively modify the structure of contaminated soil, strengthen its resistance in each aspect, thus realizing the effect of resisting heavy metal pollution.